2007
DOI: 10.1037/0893-164x.21.4.570
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent brief versus intensive smoking intervention during alcohol dependence treatment.

Abstract: Alcohol dependent smokers (N = 118) enrolled in an intensive outpatient substance abuse treatment program were randomized to a concurrent brief or intensive smoking cessation intervention. Brief treatment consisted of a 15-minute counseling session with 5 min follow-up. Intensive intervention consisted of three one-hour counseling sessions plus eight weeks of nicotine patch therapy. The cigarette abstinence rate, verified by breath CO, was significantly higher for intensive (27.5%) versus brief (6.6%) treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…The results showed worse drinking outcomes in the delayed group and no differences in smoking cessation rates (19 and 8% at week 20). A more recent study provided either brief or intensive smoking cessation treatment concurrently with alcohol dependence treatment and reported 9.1% smoking abstinence at 6 months when an intensive intervention was delivered [38] . Discrepancies in the findings of the four studies may be due to methodological differences, as suggested in a previous review [51] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed worse drinking outcomes in the delayed group and no differences in smoking cessation rates (19 and 8% at week 20). A more recent study provided either brief or intensive smoking cessation treatment concurrently with alcohol dependence treatment and reported 9.1% smoking abstinence at 6 months when an intensive intervention was delivered [38] . Discrepancies in the findings of the four studies may be due to methodological differences, as suggested in a previous review [51] .…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that patients with relatively short periods of alcohol abstinence at baseline tend to struggle with both types of abstinence [30] . However, most studies examining the risk of alcohol and/or non-nicotine drug relapse suggest that concurrent treatment does not increase the probability of relapse [4,27,[31][32][33][34][35][36][37][38] . Furthermore, we also found empirical evidence that suggests smoking cessation efforts may result in improved alcohol-related outcomes [4,39] .…”
mentioning
confidence: 99%
“…A mail survey conducted in 1999 and 2000 of substance abuse treatment programs across the United States found that most of the programs routinely assessed tobacco use, but only a small proportion provided tobacco cessation in the treatment plans of youth (Kurst-Swanger & Stockweather, 2003). The belief that quitting smoking while attempting to quit other substances may increase the risk of relapse is pervasive (Bernstein & Stoduto, 1999;Ziedonis, Guydish, Williams, Steinberg, & Foulds, 2006), despite growing empirical evidence that tobacco cessation efforts with adults do not negatively impact recovery (Reid et al, 2008) and in fact may be associated with more positive substance abuse treatment outcomes (Brown et al, 2009;Cooney et al, 2007;Friend & Pagano, 2004;Kohn, Tsoh, & Weisner, 2003;Prochaska, Delucchi, & Hall, 2004). However, the literature on adolescents is more limited (de Dios, Vaughan, Stanton, & Niaura, 2009;Myers & Brown, 1997;Myers & Brown, 2005;Myers & Prochaska, 2008;Myers et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…In the VHA, front-line therapies for tobacco cessation on the National Formulary include nicotine replacement therapy (NRT), bupropion and combination therapy [37]. NRT during SUD treatment reduces cigarette consumption and increases the likelihood of tobacco abstinence [30,32,38,39]. NRT also helps to prevent tobacco relapse in patients with a history of alcohol misuse [4,40,41].…”
Section: Introductionmentioning
confidence: 99%